Fundamental Implementation of Green Open Space Function Arrangement in Gorontalo City - Novita Daud; Dian Ekawaty Ismail; Nirwan Junus (Universitas Negeri Gorontalo, 2021)
This study aims to find out and analyze the effectiveness of structuring the function of the Green Open Ruan in Gorontalo City, as well as to find out the factors that hinder the availability of Green Open Space in Gorontalo City. The type of research used is empirical research where this research places a system of statutory norms when interacting with the community. Next described in the descriptive form to explain the results of the study. The research obtained by the authors in conducting this study includes the arrangement of Green Open Space in the City of Gorontalo, which provides ecological, socio-cultural, aesthetic, and economic benefits. However, it has not been maximized because the availability of Gorontalo City Green Open Space does not reach the standard compared to the overall Green Open Space area that has been set. Furthermore, based on the results of research obtained, the obstacles encountered in efforts to realize Green Open Space, namely barriers to inadequate land availability, as well as low community culture in maintaining and preserving urban Green Open Space.